2009
DOI: 10.3762/bjoc.5.53
|View full text |Cite
|
Sign up to set email alerts
|

Iridium-catalyzed asymmetric ring-opening reactions of oxabicyclic alkenes with secondary amine nucleophiles

Abstract: SummaryIridium-catalyzed asymmetric ring-opening reactions of oxabicyclic alkenes with various aliphatic and aromatic secondary amines are reported for the first time. The reaction gave the corresponding trans-1,2-dihydronaphthalenol derivatives in good yields with moderate enantioselectivities in the presence of 2.5 mol % [Ir(COD)Cl]2 and 5 mol % bisphosphine ligand (S)-p-Tol-BINAP. The trans-configuration of 3f was confirmed by X-ray crystallography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…IR (KBr, cm -1 ): 3233 (s), 3057 (w), 3014 (m), 1601 (s), 1498 (s), 1450 (w), 1425 (w), 1312 (m), 1185 (m), 1046 (m), 783 (s), 695 (s). 1 H NMR (400 MHz, CDCl 3 ): δ 7.47 (d, J=6.4 Hz, 1H), 7.29 (t, J = 5.6 Hz, 2H), 7.21 (t, J = 7.6 Hz, 2H), 7.15 (d,J = 6.4 Hz,1H),6.78 (t,J=6.8 Hz,1H),6.71 (d,J=7.6 Hz,2H),6.56 (d,J=9.6 Hz,1H),6.01 (d,J=7.2 Hz,1H),4.84 (d,J= 7.6 Hz,1H),4.31 (d,J = 4.4 Hz,1H),3.37 (s,1H), 2.60 (s, 1H); 13 C NMR (100 MHz, CDCl 3 ): δ 146. 6, 135.6, 131.9, 129.5, 128.5, 128.5, 128.2, 128.0, 127.0, 126.7, 118.4, 114.1, 71.5, 55.6.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IR (KBr, cm -1 ): 3233 (s), 3057 (w), 3014 (m), 1601 (s), 1498 (s), 1450 (w), 1425 (w), 1312 (m), 1185 (m), 1046 (m), 783 (s), 695 (s). 1 H NMR (400 MHz, CDCl 3 ): δ 7.47 (d, J=6.4 Hz, 1H), 7.29 (t, J = 5.6 Hz, 2H), 7.21 (t, J = 7.6 Hz, 2H), 7.15 (d,J = 6.4 Hz,1H),6.78 (t,J=6.8 Hz,1H),6.71 (d,J=7.6 Hz,2H),6.56 (d,J=9.6 Hz,1H),6.01 (d,J=7.2 Hz,1H),4.84 (d,J= 7.6 Hz,1H),4.31 (d,J = 4.4 Hz,1H),3.37 (s,1H), 2.60 (s, 1H); 13 C NMR (100 MHz, CDCl 3 ): δ 146. 6, 135.6, 131.9, 129.5, 128.5, 128.5, 128.2, 128.0, 127.0, 126.7, 118.4, 114.1, 71.5, 55.6.…”
Section: Discussionmentioning
confidence: 99%
“…The structures of the ring-opening products were determined and characterized by 1 H and 13 C NMR, IR, HRMS, and elemental analysis. We found that these products possess a trans configuration.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Over the years, several interesting transformations have been investigated such as cycloadditions 4 [18][19][20][21][22][23], dimerizations 3 [24][25][26][27], isomerizations [28][29][30][31], among other reactions that have been reported [32][33][34][35][36][37][38]. The nucleophilic ring-opening reactions of heterobicyclic alkenes are of particular interest [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53], as they provide access to a broad family of synthetic building blocks bearing multiple stereocenters in a single step 2 [54]. Application of these functionalized intermediates have found use in the total synthesis of (+)-norchelidonine (an isoquinoline alkaloid) [55], sertraline (an antidepressant) [56], and arnottin I (an antiinflammatory) [57].…”
Section: Introductionmentioning
confidence: 99%
“…Halide and triflate salts such as NH 4 F, Et 3 N∙HCl, NH 4 Br, NH 4 I, Bu 4 NI, and AgOTf were also used as additives to enhance the enantioselectivities of the ARO reaction. Recently, our group demonstrated that iridium-catalyzed asymmetric ring-opening of oxa- and azabicyclic alkenes with nitrogen- or oxygen-based nucleophiles, such as amines, alcohols, phenols and Grignard reagents [62,63,64,65,66,67,68,69,70,71,72,73,74]. Furthermore, a new iridium-monophosphine catalyst was found to be efficient for asymmetric ring-opening of benzonorbornadiene with amines, providing a series of chiral substituted dihydronaphthalenes in high yields (up to 98%) and excellent enantioselectivities (>99% ee ) [71].…”
Section: Introductionmentioning
confidence: 99%